Tangible and Intangible Cultural Heritage in Support to Post-war Biak Tourism - Evi Aryati Arbay,; Bambang Shergi Laksmono, (Technium Social Sciences Journal, 2020)
The Biak battle was part of World War II and fought by the United States Army and the Japanese Army in 1944. Out of the 24,000 soldiers from both sides involved in the war, 6,600 were killed; 6,100 of them were the Japanese soldiers. Remnants of war and remains of the fallen soldiers scattered in post-war Biak. The war zone then started to get visits from the Japanese for pilgrimage, remnants of war were unearthed and human remains were cremated and repatriated. The battlefield drew more tourists’ interest for the dark tourism experience. Remnants of war became valuable tangible items while war history and mystical cave atmosphere became intangible items. The study aimed at exploring issues in importance and preservation of tangible and intangible in support to post-war Biak tourism. It turned out that the post-war tangible and intangible heritage in Biak require better handling and management in support to post-war Biak tourism sustainability.